Jaga Jarak, Jauhi Kerumuman! Antara Kepatuhan Lampau, Motivasi, Niat Terhadap Protokol Pembatasan Fisik - Cleoputri Yusainy; Alfi Nur Fauziyyah; Amira Latinsadina; Wahyu Wicaksono (Airlangga University Press, Universitas Airlangga, 2023)
Physical presence is crucial in almost every social event in Indonesia, but could potentially inhibit obedience to physical distance protocol during COVID-19 pandemic. This study (N = 114 undegraduates, 62,3% female; M age = 21,69; SD = 2,19) explored the extent to which adherence of physical distance could be predicted by three social-cognitive factors from the Theory of Planned Behaviour (i.e., attitude, subjective norm, and perceived behavioural control), autonomy motivation from the Self-Determination Theory, and past adherence behaviour. We found that 68.02% of the variance in intention to perform physical distancing in the future was predicted by autonomy motivation, attitude, and perceived behavioural control explained. Moreover, after accounting autonomy motivation the role of subjective norm and past adherence behavior were no longer significant. It is therefore timely to shift focus from merely reporting past adherence behaviour to promoting an individual’s autonomy motivation.